2018
DOI: 10.1001/jamasurg.2018.1039
|View full text |Cite
|
Sign up to set email alerts
|

Association of Opioid-Related Adverse Drug Events With Clinical and Cost Outcomes Among Surgical Patients in a Large Integrated Health Care Delivery System

Abstract: Opioid-related adverse drug events were common among patients undergoing hospital-based invasive procedures and were associated with significantly worse clinical and cost outcomes. Hospital-acquired harm from ORADEs in the surgical patient population is an important opportunity for health systems to improve patient safety and reduce cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
159
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(170 citation statements)
references
References 22 publications
11
159
0
Order By: Relevance
“…creases in clinical outcomes and overall healthcare utilisation associated with prescription opioid use, in particular the disproportionate increased risk among persons with CLD. Our findings validate the association of opioid use and higher rates of admission and overall mortality found in prior, small single centre retrospective studies and in larger database studies of the general population 7,10,20,21. In our study, individuals with CLD and opioid prescriptions had a 2.5 times increased risk of hospitalisation and a 1.95 times increased risk of in-hospital mortality compared to individuals without CLD with opioid prescriptions.…”
supporting
confidence: 90%
“…creases in clinical outcomes and overall healthcare utilisation associated with prescription opioid use, in particular the disproportionate increased risk among persons with CLD. Our findings validate the association of opioid use and higher rates of admission and overall mortality found in prior, small single centre retrospective studies and in larger database studies of the general population 7,10,20,21. In our study, individuals with CLD and opioid prescriptions had a 2.5 times increased risk of hospitalisation and a 1.95 times increased risk of in-hospital mortality compared to individuals without CLD with opioid prescriptions.…”
supporting
confidence: 90%
“…In a study of 135,379 surgical patients having a wide variety of procedures and endoscopy, inpatient opioid use resulted in 11%e14% ORAE and was associated with increased inpatient mortality, an increase in hospital length of stay (LOS), higher 30-day readmission rate, and an $8225 increase in hospital episode cost. 14 Another study found that patients who were prescribed opioids after low-risk surgery were 44% more likely to receive opioids one year postoperatively compared to those not receiving opioids. 23 Though opioid-prescribing patterns are likely to vary among hospitals and surgeons, we found that the MIS approach in sigmoid resection reduced both the dose of opioids received and the duration of combined opioid use (parenteral and/ or oral) in the perioperative period.…”
Section: Discussionmentioning
confidence: 99%
“…12 Approximately 10% of patients undergoing surgery develop opioid-related adverse events (ORAE) that are associated with increase inpatient mortality, prolonged length of stay, increased cost of hospitalization, and higher readmission rates. 13,14 Patients undergoing gastrointestinal surgery have moderate to severe pain and are at higher risk for prolonged postoperative use of opioids when compared to other procedures. 2,10 Previous studies have shown that the minimally invasive surgical (MIS) approach is associated with less postoperative pain and analgesic needs than the open approach (OS) in patients with colon or rectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Opioid analgesics are commonly used to manage moderate to severe acute pain among hospital inpatients . The National Institute for Health and Care Excellence identified opioids as a high‐risk medicine as they account for up to 16.1% of hospital adverse drug events (ADEs) . Opioid‐related ADEs include constipation, nausea, sedation and respiratory depression.…”
Section: Introductionmentioning
confidence: 99%